Relative second language proficiency and the giving and receiving of written peer feedback. (February 2016) - Allen, David; Katayama, Akiko
Abstract: Peer feedback is a potentially beneficial yet highly complex process that can be influenced by a variety of social, historical and cultural factors. Here, we focus on learner proficiency and learners' perceptions of their own and their peer's proficiency, in addition to other factors, and we describe how these factors may influence the quantity and type of feedback given and utilized during feedback sessions. In the context of an undergraduate academic writing course, data was collected from six undergraduate Japanese learners of English who participated in dyadic peer feedback. Written texts, interview data and classroom observation formed a triangulated data set that was used to inform our inquiry. The writers' initial and revised drafts and the reviewers' comments were used in individual interviews as a basis for discussing the feedback process and the factors that influenced it. Differences in language proficiency and perceived relative proficiencies of the peers appeared to be important factors influencing the process. The results of the study are discussed with reference to pedagogical applications during peer feedback.